1986
DOI: 10.1021/bi00365a008
|View full text |Cite
|
Sign up to set email alerts
|

Motion at the active site of [(4-fluorophenyl)sulfonyl]chymotrypsin

Abstract: Fluorine and deuterium NMR relaxation studies have been used to examine the motion of the 4-fluorophenyl ring attached to the active site of [(4-fluorophenyl)sulfonyl]-alpha-chymotrypsin at pH 4. Analysis of the results indicates that rotation about the 2-fold axis of this ring is reasonably rapid, though not as fast as in tosylchymotrypsin. Two-dimensional (2D) nuclear Overhauser effects (NOEs) were used to suggest the shifts of those protons of the enzyme close enough to the fluorine nucleus to lead to relax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…As is apparent from this figure, each of the fluorine resonances which appear in the 19F NMR spectrum of the 5-fluorotryptophan-labeled enzyme (Luck and Falke, 1991a) is now doubled. The observed isotope-shift value of-0.58 ppm is approximately double the value of-0.262 ppm, which has been reported for each ortho-deuterium substitution in the [3,5-2H2]-4-fluorobenzenesulfonyl fluoride (Ando et al, 1986), and is also consistent with the 7-deuterium isotope shifts observed in fluoroethanes (Osten et al, 1985). The resonances due to FTrp 133 now appear as three separate peaks due to the combined effects of the conformational shift (Av = 0.65 ppm) and the isotope shift, with the resonance furthest upfield overlapping one of the FTrp 284 resonances.…”
Section: Resultsmentioning
confidence: 47%
“…As is apparent from this figure, each of the fluorine resonances which appear in the 19F NMR spectrum of the 5-fluorotryptophan-labeled enzyme (Luck and Falke, 1991a) is now doubled. The observed isotope-shift value of-0.58 ppm is approximately double the value of-0.262 ppm, which has been reported for each ortho-deuterium substitution in the [3,5-2H2]-4-fluorobenzenesulfonyl fluoride (Ando et al, 1986), and is also consistent with the 7-deuterium isotope shifts observed in fluoroethanes (Osten et al, 1985). The resonances due to FTrp 133 now appear as three separate peaks due to the combined effects of the conformational shift (Av = 0.65 ppm) and the isotope shift, with the resonance furthest upfield overlapping one of the FTrp 284 resonances.…”
Section: Resultsmentioning
confidence: 47%
“…Fluorescence correlation spectroscopy indicates that the rotational correlation time for CA I should be 12-15 ns (Kask et al, 1987). If one assumes a standard geometry for the nuclei attached to the aromatic ring of I and assumes that a proton of the enzyme comes within van der Waals contact of the fluorine nucleus of the inhibitor, the relaxation of the fluorine nucleus of a bound inhibitor molecule should be similar to that deduced for [(4-fluorophenyl)sulfonyl]chymotrypsin (Ando et al, 1986) where the fluorine Tx and NOE values and the rotational correlation time are all similar to those found for carbonic anhydrase. In the case of the chymotrypsin derivative, it was concluded that rotation of the aromatic ring holding the fluorine atom was significantly hindered, being characterized by a correlation time slightly smaller than that for overall tumbling of the protein.…”
Section: Discussionmentioning
confidence: 93%
“…It has been frequently observed that fluorine linewidths in protein systems are substantially broader than would be anticipated from spin-lattice relaxation behavior (for examples see Kimber et ah (1977), Post et al (1984), and Ando, Gerig and Luk (1986)) and we ignored the linewidth data in attempting to analyze the dynamics of these systems. Relaxation of aromatic fluorine of IV in the presence of the enzyme was examined by setting up a program to compute T i relaxation behavior and time dependence of tgF{tH} NOE formation using the model system described above.…”
Section: Resultsmentioning
confidence: 99%